Zum Vorkommen der auf Säugetieren parasitierenden Lausfliegen in der Uckermark (Diptera, Hippoboscidae). - Jentzsch, Matthias; Menzel, Frank (Contributions to Entomology = Beiträge zur Entomologie, 2010)
Louse flies (Hippoboscidae) were collected from 20 different wooded areas in the Uckermark region (north-east Germany). The specimens were taken from Diptera samples caught during a reseach project »Nordmitteleuropa 2020« (NME 2020) in 2001 to 2003. As a result of this, the louse flies Hippobosca equina Linnaeus, 1758 and Lipoptena cervi (Linnaeus, 1758) were identified from the Uckermark. Only females were found and they were exclusively winged and probably seeking vectors. Both species generally parasitise large mammals (H. equina mainly domestic horses, L. cervi mainly deer) and both species are usually common and widespread. This evidence makes a valuable contribution to the louse fly fauna of Brandenburg and Mecklenburg-Vorpommern. Keywords Diptera, Hippoboscidae, Germany, Brandenburg, Mecklenburg-Vorpommern, Uckermark, faunistics, new records.